Nilai-Nilai Dasar Hak Asasi Manusia dalam Konsep al-Maqâshid al-Syarî‘ah - Huda, Muhammad Hasbulloh (MAQASHID, 2018)
The values ??of human rights are not something new, we can find the values ??of human rights principles in the concept of Maq?shid al-Shar?'ah which is the foundation of the building of Islamic law itself. In this article the author seeks to explore the basic values ??of human rights in Islamic law by focusing on the theories of Maqashid al-Shari'ah. Some of the principal values ??that we can meet include the principle of justice, the principle of guaranteed protection, the principle of respect for rights, the principle of brotherhood, and the principle of freedom.